Serum Proteome Analysis in Patients with Rheumatoid Arthritis Receiving Therapy with Tocilizumab: An Anti-Interleukin-6 Receptor Antibody. (22nd August 2013) - Yanagida, Mitsuaki; Kawasaki, Mikiko; Fujishiro, Maki; Miura, Masako; Ikeda, Keigo; Nozawa, Kazuhisa; Kaneko, Hiroshi; Morimoto, Shinji; Takasaki, Yoshinari; Ogawa, Hideoki; Takamori, Kenji; Sekigawa, Iwao
Abstract : Rheumatoid arthritis (RA) is a chronic inflammatory disorder of the synovial membrane that results in the destruction of bone and cartilage in affected joints. Tocilizumab is a biological agent and an anti-interleukin-6 (IL-6) receptor monoclonal antibody that blocks IL-6-mediated inflammatory processes in RA patients. In order to identify novel disease-related proteins and candidate biomarkers, we analyzed the changes in the serum proteome profiles of patients with RA who were treated with tocilizumab. Serum samples were collected from the RA patients before and after tocilizumab treatment. Following immunodepletion of major proteins, the proteins were digested and labeled with isobaric tag, iTRAQ reagent. The proteins were identified and quantified using liquid chromatography-tandem mass spectrometry. Among a total of 311 proteins identified, seven were decreased and 16 were increased by tocilizumab treatment. Although some of the proteins are known to be related to RA, several are currently unknown with respect to their relationship to RA and may be involved in the development of this disease. This study is the first to perform a comparative serum proteomic analysis of RA patients treated with tocilizumab. Our results may contribute to the identification of novel disease-related proteins and enhance the understanding of the pathogenesis of RA.